Combination product of dermal matrix, preconditioned human mesenchymal stem cells and timolol promotes wound healing in the porcine wound model. Issue 7 (31st January 2022) - Yang, Hsin‐ya; Fierro, Fernando; Yoon, Daniel J.; Gallegos, Anthony; Osborn, Stephanie L.; Nguyen, Alan V.; Peavy, Thomas R.; Ferrier, William; Talken, Linda; Ma, Betty W.; Galang, Kristopher G.; Medina Lopez, Andrea; et al.
Abstract: A combination product of human mesenchymal stem/stromal cells (MSCs) embedded in an extracellular matrix scaffold and preconditioned with hypoxia and the beta‐adrenergic receptor antagonist, timolol, combined with sustained timolol application post implantation, has shown promising results for improving wound healing in a diabetic mouse model. In the present study, we extend those findings to the more translatable large animal porcine wound model and show that the combined treatment promotes wound reepithelialization in these excisional wounds by 40.2% and increases the CD31 immunostaining marker of angiogenesis compared with the matrix control, while maintaining an accumulated timolol plasma concentration below the clinically safe level of 0.3 ng/mL after the 15‐day course of topical application. Human GAPDH was not elevated in the day 15 wounds treated with MSC‐containing device relative to wounds treated with matrix alone, indicating that the xenografted human MSCs in the treatment do not persist in these immune‐competent animals after 15 days. The work demonstrates the efficacy and safety of the combined treatment for improving healing in the clinically relevant porcine wound model. Abstract : Applying a combination treatment as shown in steps 1–3, MSCs preconditioned in timolol at hypoxia on wound scaffolds (MSC‐scaffold) with daily topical timolol solution to wounds, improves wound healing in a porcine model. The treatment promotes reepithelialization in the excisional wounds by 40.2% and increases angiogenesis by elevating CD31 immunostaining compared with the control, while the accumulated timolol concentration detected in plasma remains below the clinically safe level of 0.3 ng/mL after the 15‐day course of treatment.